Coping with Homelessness: An Expectant Mother's Homeless Pathway. Issue 3 (20th August 2014) - Moore, Russell David
Abstract : Purpose: The paper aims to add to the understanding of homelessness by exploring and analysing the homeless pathway of a young expectant mother as she negotiates her way through temporary accommodation and comes to terms with her circumstances and new identity as a person without a home. Design/methodology/approach: A phenomenological interviewing approach was used in order to gain insights into the subject's lived daily world from their perspective. Themes were then identified that encapsulated the essential qualities of the interview. Findings: The stress and negative emotions of being homeless appear to be accentuated significantly due to pregnancy, taking the potential for the positive feelings associated with pregnancy away from the participant. Structural factors such as the homelessness legislation and affordable housing supply had a strong influence over her homeless pathway, resulting in feelings of a loss of control over her destiny and choices and subsequent feelings of low self-worth, which she had to try to come to terms with. However, the pregnancy was also used as a positive coping strategy, as was family support. Originality/value: Minimal research has been undertaken on the experiences of homeless women who are pregnant. The results point to the need to understand the deeply negative impacts that homelessness can have on individuals, particularly expectant mothers. The value of examining homelessness as a pathway is also shown.